2017
DOI: 10.1002/path.4896
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib has antitumour effects on Pten‐deficient endometrial neoplasias

Abstract: PTEN is one of the most frequently mutated genes in human cancers. The frequency of PTEN alterations is particularly high in endometrial carcinomas. Loss of PTEN leads to dysregulation of cell division, and promotes the accumulation of cell cycle complexes such as cyclin D1-CDK4/6, which is an important feature of the tumour phenotype. Cell cycle proteins have been presented as key targets in the treatment of the pathogenesis of cancer, and several CDK inhibitors have been developed as a strategy to generate n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Different Akt and mTOR inhibitors have been tested in transgenic mice, showing good responses [106,109]. Recent preclinical studies using transgenic EC mice tested olaparib (PARP-inhibitor) [107], dienogest (fourth-generation progestin) [117], and palbociclib (CDK4,6 inhibitor) [118]. Such models have also been used to evaluate the effect of diet on EC tumorigenesis, showing that the elevation of ω-3-polyunsaturated fatty acids attenuates PTEN deficiency-induced EC development [119].…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…Different Akt and mTOR inhibitors have been tested in transgenic mice, showing good responses [106,109]. Recent preclinical studies using transgenic EC mice tested olaparib (PARP-inhibitor) [107], dienogest (fourth-generation progestin) [117], and palbociclib (CDK4,6 inhibitor) [118]. Such models have also been used to evaluate the effect of diet on EC tumorigenesis, showing that the elevation of ω-3-polyunsaturated fatty acids attenuates PTEN deficiency-induced EC development [119].…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…In EC, Dosil et al [60] performed the first preclinical study to test the therapeutic potential of palbociclib; specifically, this was tested in the endometrial malignancies driven by Pten deficiency. This work started with the assessment of palbociclib response in vitro and in a PTEN-deficient GEM model and was finally validated in a PTEN-mutated PDX model of endometrioid EC of FIGO stage IIIC and grade 2.…”
Section: Endometrial Cancer Pdx Modelsmentioning
confidence: 99%
“…This work started with the assessment of palbociclib response in vitro and in a PTEN-deficient GEM model and was finally validated in a PTEN-mutated PDX model of endometrioid EC of FIGO stage IIIC and grade 2. This work evidenced that palbociclib has therapeutic potential as an anticancer drug in the endometrium, since it reduces tumour cell proliferation and disrupts the tumourigenesis process [60]. …”
Section: Endometrial Cancer Pdx Modelsmentioning
confidence: 99%
“…The enhanced understanding of PTEN function in controlling progression through the first gap phase (G1) of the cell cycle has implications for cancer treatment. For example, based on the prevailing upregulation of cyclin D1 following PTEN loss, a recent preclinical study demonstrated a significant therapeutic effect of cyclin D1-Cdk4/6 inhibition in a Pten -deficient endometrial tumor model [70]. In summary, PTEN inhibits the G1-S transition to prevent premature progression to DNA replication and resultant CIN.…”
Section: Role Of Pten Within the Cell Cycle: Guard Phase Transitions mentioning
confidence: 99%